Not all lexical access tasks are created equal: Lexical development between three and five. Issue 1 (February 2014) - Isacoff, Nora M.; Stromswold, Karin
Lexical access tasks are designed to measure efficiency of lexical access, but task demands and methods vary greatly. Many lexical access tasks do not account for confounding factors including competence in other linguistic abilities. In this study, preschoolers were given two lexical access tasks. In the single-category naming (SCN) task, children rapidly named animals. In the multi-category naming (MCN) task, children named one item from each of 10 categories. Children were also tested on vocabulary, syntax, and articulation. First, scores on each task increase with age. Second, the two lexical access scores were only moderately correlated, suggesting that different 'lexical access' tasks measure different abilities. Finally, we compared scores on each of the lexical access tasks with scores on the other linguistic tasks, demonstrating that different linguistic abilities are involved in each task at different ages. Results suggest that even very similar tasks capture different aspects of lexical access, and that the SCN task is a purer lexical access test.